Suicide Ideation, School Absenteeism and Physical Violence among Secondary School Students in Kampala, Uganda - Samuel Sendagala; John Senkusu; George William Lubwama; Danstan Bagenda; Micheal Muyonga; Wolfgang Hladik (Intelektual Pustaka Media Utama, 2018)
School youth in many African countries face a range of non-infectious health risks, in addition to the infectious disease burden typical in resource-limited settings. We examined self-reported health behaviors associated with suicide ideation, school absenteeism and physical violence among secondary school students in Kampala, Uganda. We conducted a cross-sectional three-stage cluster-based survey among students aged >=15 years, and/or enrolled in forms 3–6 (grades 9-12) in 54 secondary schools in Kampala. Interview data were collected with a standardised electronic questionnaire through computer-assisted self-interviewing and results were weighted for sample design and non-response. Pearson’s chi-square and logistic regression methods were used for bivariate and multivariate analysis respectively. Bullying among female respondents was positively associated with suicide ideation (aOR=1.73). In multivariate analysis, suicidal ideation was positively associated with a lifetime exposure to illicit drug use (aOR=1.76), serious injury (aOR=1.67) or school absenteeism (aOR=1.46). School absenteeism was positively associated with serious injury (aOR=1.59), history of alcohol consumption (aOR=1.55), bullying (aOR=1.52) and suicide ideation (aOR=1.45). Serious injury (aOR=2.89), a life-time history of illicit drug use (aOR=2.65), recent history of having been bullied (aOR=2.38), physical activity (aOR=2.12), suicide ideation (aOR=1.58), school absenteeism (aOR=1.57) were associated with having been engaged in physical violence. Bullying, serious injury and illicit drug use were associated with suicidal ideation, school absenteeism and physical violence. Concerted efforts should be considered by education authorities, parents and the community to tackle these risky behaviors.